Impulsiveness/venturesomeness and coping stress strategies in handball - Simic, N.; Mesic, M. (Croatian Sports Medicine Journal, 2014)
The aim of this study was to examine the relationship between personality traits impulsiveness, venturesomeness and coping stress strategies in male and female handball players. Examination was conducted on a sample of 73 male and 77 female handball players, 14-35 years old (M = 17.68, SD = 3.87, min. = 14, max. = 35). Sociodemographic questionnaire, Eysenck's Impulsiveness Questionnaire (EPQ - IVE) and Coping Inventory for Stressful Situations by Endler and Parker (CISS) were applied. Results showed statistically significant differences in personality traits with respect to gender. Female handball players attained significantly higher scores on scales of impulsivity. Statistical analysis also showed significant differences in coping stress strategies. Female more than male handball players chose styles focused on emotions, avoidance and social diversion. However, there is no differences between personality traits and sports experience. But there are statistically significant differences between experience and coping styles. Players with more handball experience chose avoidance, social diversion and problem oriented coping styles.